KUALITAS SIA DAN USER SATISFACTION SIA DI PRODI BUSSINESS ENGLISH FBS UNM - Riny Jefri (Seminar Nasional LP2M UNM, 2019)
The purpose of this study was to examine the effect of the quality of the SIA system on user satisfaction Sistem Informasi Akademik (SIA) at Universitas Negeri Makassar (UNM). This study uses multiple regression analysis and uses samples of business English study programs that are active in the Faculty of Language and Literature. This study generates support for previous studies that use the variable reliability, Ease of use, flexibility and functionality to measure the quality of information systems, that the quality of the information system influences the satisfaction of SIA users in the Business Study Program of FBS UNM which is active in Odd Semester 2016/2017. The results of this study are expected to help managers of Higher Education information systems in order to improve the quality of information systems that exist in the tertiary environment so as to increase the satisfaction of users of the information system itself maximally.